Violence and exploitation of young women: Mobility and strengthening of networks of Albanian prostitution - Chassagne Philippe; Gjeloshaj Kolë (Temida)
Big mobility of groups of Albanian organized crime and their systematic, and sometimes extreme use of violence has probably two elements, which can explain the increase of exploitation of prostitution committed by Albanian criminals in Western Europe. They became inevitable in trafficking in women from Central and Eastern Europe for prostitution in Western Europe. They are located in the centers of recruitment, in transport channels as well as in forced sexual exploitation. The analysis of the above-mentioned situation is the subject of this paper.